PENINGKATAN USAHA DAN PENDAMPINGAN PIRT SERTA SERTIFIKASI HALAL ABON IKAN WALASOJI - Rusdi Nur; Muhammad Arsyad; Sirajuddin Omsa (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The Walasoji Shredded Fish (AIW) Business Community was located in Rappang Village, Panca Rijang District, Sidenreng Rappang Regency, South Sulawesi, started its activities in 2012. The partner community is a home industry, initially having around eight members, but now there are only three people. In the shredded production process, partners still use traditional tools, partners cannot determine the exact profit, the packaging of shredded products is still simple without a brand, without a health department permit number, and without a halal certificate from MUI. The problems faced by partners are: how to improve the quality and production capacity, how to know the profit for sure, how to increase the market share of shredded walasoji fish. Based on the problems above, the solution is to improve production methods and processes using machines, provide training and counseling on management, as well as a simple accounting bookkeeping system, assist in branding and packaging equipment, assist in obtaining permits from the health department, and MUI halal certificates. Through this PKM, it is hoped that the capacity and quality of AIW produced by partners will increase, and can be marketed through markets, shops, supermarkets and supermarkets. The methods that will be applied are assistance with production equipment, and packaging, training and counseling on management, and a simple accounting system, assisting in obtaining permits from the health department, and MUI halal certificates. The output targets to be achieved in this activity are scientific publications in national journals or proceedings of national seminars, and published in print or online mass media. With the publication, it is targeted that AIW, which is only known in Rappang, can be widely known, both regionally and nationally after this PKM is implemented.